2009
DOI: 10.11124/jbisrir-2009-554
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the effectiveness of primary health education or intervention programs in improving rural womenʼs knowledge of heart disease risk factors and changing lifestyle behaviours.

Abstract: Background Cardiovascular disease is the leading cause of death and disability for women in Australia. Women living in rural areas are at greater risk of heart disease, because of limited access and availability of healthcare in rural areas. Lifestyle is a major determinant to the risk of heart disease. Risk factors such as smoking, hypertension, diet, physical activity and alcohol intake can be controlled or modified by lifestyle changes. As heart disease develops over many years, women need to be following h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
7
0
1
Order By: Relevance
“…The notion that a careless diet is a risky lifestyle has been a motto for several studies. A systematic review on the effectiveness of training programs in primary health care has shown that there is improvement in eating habits and consequently in health outcomes, given the interventions regarding a balanced diet (15) .…”
Section: Discussionmentioning
confidence: 99%
“…The notion that a careless diet is a risky lifestyle has been a motto for several studies. A systematic review on the effectiveness of training programs in primary health care has shown that there is improvement in eating habits and consequently in health outcomes, given the interventions regarding a balanced diet (15) .…”
Section: Discussionmentioning
confidence: 99%
“…An example of a regular fitness routine was walking 30 minutes each day. Crouch et al 14 examined intervention programs' effects in a systematic review in rural Australian women. Studies targeting physical activity reported activity increased, and these increases were sustained at one year.…”
Section: Discussionmentioning
confidence: 99%
“…Penatalaksanaan awal dari SM yang dapat dilakukan di masyarakat yaitu dengan perubahan gaya hidup, misalnya mengurangi makanan berlemak, meningkatkan aktivitas fisik, serta mengontrol berat badan secara teratur. 14,15 Beberapa hasil penelitian, baik di negara maju maupun di negara berkembang, menunjukkan adanya hubungan signifikan antara pengetahuan, sikap, dan tindakan (PST) terkait gaya hidup sehat dengan risiko SM dan PKV, seperti di Iran, 1 , Srilanka, 17 Australia, 18 dan Jepang. 15 Di Indonesia, penelitian mengenai SM dan PKV ini telah banyak dilakukan.…”
Section: Pendahuluanunclassified